Підвищення кадрової складової трудових ресурсів - Лісіна, Світлана; Пелипишин, Галина (Видавництво Львівської політехніки, 2019)
External certification of workplace skills obtained through on-the-job training is widespread in many countries. This may indicate that training is financed by workers, and certification serves to assure the quality of the training offered by the firm. External certification of training may also be necessary for an equilibrium with firm-sponsored training.
Keywords: кадровий потенціал; трудові ресурси; відділ кадрів; підвищення кваліфікації; кадри